Reforming Qardh Practices in Islamic Banking : A Critical Analysis Based on Jasser Auda’s Maqāṣid al-Sharīah Systems Approach in Indonesia - Mohammad Ghozali; Khusniati Rofiah; Khurun'in Zahro'; Mualimin Mochammad Sahid (STAIN Ponorogo, 2026)
Non-Indexed Publication